The Effectiveness of Using Digital Transaction Applications with the Technology Acceptance Model for Financial Management - Kusumawati, Evi Dewi; Putri, Eskasari (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: This study aims to examine the effectiveness of digital transaction applications in managing finances for small and medium-sized enterprises (SMEs) in the culinary industry. Methodology: The Technology Acceptance Model (TAM) was used to analyze the factors influencing the adoption of digital transaction applications among SMEs. Finding: The results show that perceived usefulness, perceived ease of use, and attitude towards using digital transaction applications have a positive impact on the intention to use these applications. The study also found that external factors, such as individual factors and social factors, influence the adoption of digital transaction applications. Implication: The findings of this study have implications for the development of digital transaction applications that are tailored to the needs of SMEs in the culinary industry. Originality: This research is original because it combines the Technology Acceptance Model (TAM) with external factors such as individual and social factors to analyze the adoption of digital transaction applications in the MSME culinary industry. Keywords: Accounting Information System, Digital Transaction Application, Technology Acceptance Model.